Complete mitochondrial genome and phylogenetic analysis of Schizothorax sinensis (Teleostei: Cypriniformes: Cyprinidae). Issue 3 (4th March 2021) - Chen, Deng; Fu, Changkun; Lei, Ziyong; Li, Yuhao; Zhao, Tianmeng; Fan, Hailing; Hu, Tao; Wang, Qian; Zong, Hao
Abstract: This study describes the first sequencing of the complete mitochondrial genome of Schizothorax sinensis, a species of cyprinid snowtrout from the Jialing River and Fujiang River basins in China's Sichuan Province. The total length is 16, 571 base pairs. Similar to most Schizothoracinae mitochondrial genomes, there are 37 genes including 13 protein coding genes, 22 transfer RNA genes and 2 ribosomal RNA genes. In addition, it contains a control region rich in A-T nucleotides. The overall nucleotide composition is 29.6% for A, 27.1% for C, 17.9% for G and 25.4% for T, and the percentage of GC content is 45.0%. Phylogenetic analysis suggested that Schizothorax sinensis and Schizothorax prenanti clustered together in a clade. This work provides additional molecular information for studying Schizothorax sinensis conservation genetics and evolutionary relationships.